Sylvester not only captured Tweety - Francisco J. Perez; Gerson A. Salcedo-Rivera; Andrés Camilo Montes-Correa; Juan F. Cruz; Andrés Blanco-Narváez; Jaime De La Ossa-V.; Julio Chacón-Pacheco (Mammalogy Notes, 2022)
The domestic cat is an invasive species that creates serious problems for wildlife worldwide. For the Neotropical region there is deficiency in knowledge about hunting behavior, affected species and other aspects that allow a better understanding of the effects on local biodiversity. In this study, we made an approximation of cases of mortality of wildlife by domestic cats in the Colombian Caribbean Region. We found 107 hunting records, belonging to 31 species belonging to 24 families, 12 orders and three classes of vertebrates Amphibia, Sauropsida and Mammalia. The most affected species correspond to Cnemidophorus sp (31 cases), Columbina talcopati (16 cases) and Cnemidophorus gaigei (10 cases). Additionally, we found a hunting record of a migratory species, Porzana carolina, and two subspecies of endemic reptiles from the Colombian Caribbean region, Erythrolamprus melanotus lamari and Ameiva bifrontata divisa. These records become the first reported for Colombia, warning by the quantity and taxonomic spectrum of the potential impact that it may be generating on wildlife and its ecosystem services.